Effect of phase-equilibrium uncertainties on the process design of selected C2 and C3 alcohol separation systems: a Monte Carlo approach - Burger, Leon (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.